Case report: Fecal microbiota transplant for Clostridium difficile infection in a pregnant patient with acute severe ulcerative colitis - Wang, Hanyu; Deng, Feihong; Luo, Min; Wang, Xuehong (Frontiers in Immunology, 2024)
Ulcerative colitis (UC) is a chronic colonic mucosal inflammation characterized by reduced gut microbial diversity. Patients with UC at pregnancy are prone to suffer from severe disease progression due to the changes of hormone and immune regulation. Fecal microbiota transplant (FMT) is a promising therapy for UC and recurrent Clostridium difficile infection (CDI). However, acute severe ulcerative colitis (ASUC) treatment especially in patients at pregnancy is clinically challenging. Herein, we report a 34-year-old pregnant woman who manifested with numerous bloody stools and markedly elevated serological inflammatory indicators and was diagnosed with ASUC and concurrent CDI. The use of intravenous injection steroids and anti-TNF-α therapy failed to improve her condition. Frozen encapsulated FMT therapy was finally performed to this patient with clearly improved symptoms and indications of safe delivery without UC flares or complications, and markedly increased diversity of the gut microbiota was also shown in this patient after FMT. This report firstly describes FMT as a safe salvage therapy for a pregnant patient with CDI and ASUC refractory to intravenous steroids and anti-TNF therapy.